Interaction of temperature and stocking rate on growth and meat yield of broilers - HOWLIDER, M A R (The Indian Journal of Animal Sciences, 2014)
Male (1440) and female (1 440), 21-day-old, broiler chicks were housed in 8 environmentally controlled rooms kept at 20.3°C (3 rooms) and 23.7°C, 25.8°C or 28. 7°C (3 rooms) to determine the interaction of rearing temperature and stocking density on growth and meat yield of broilers. There were 2 pens of each sex in each room and were given a floor space of either 515cm2 or 1030cm>SUP>2/bird. From each pens 2 birds were killed and dissected when they reached average live weights of 1.5.0,2.00,2.50 and 2.75kg. The carcasses were dissected for meat content. For male and female broilers, within the achieved temperature range, feed intake and growth rate declined linearly with the rise of temperature regardless of stocking density. The rate of decline in both feed intake and growth rate appeared to be slightly greater for males than for females and greater at high stocking density than at low stocking density. Feed conversion efficiency declined and mortality increased significantly with the increase of rearing temperature was found only at high stocking density, but at low stocking density feed conversion efficiency and mortality had no relationship with temperature. Rise in rearing temperature increased eviscerated yield, dark meat and, therefore, the total meat content in the carcass regardless of sex and stocking density, but breast meat content had little relation with rearing temperature. The ratio of breast to dark meat yield, however, was reduced linearly with rising temperature in both sexes and at both stocking density. The breast: dark meat yeild was slightly higher in females than that in males and higher at low stocking density than at high stocking density at all temperatures.